Novel molecular marker associated with Tm2a gene conferring resistance to tomato mosaic virus in tomato. Issue 4 (29th May 2013) - Panthee, Dilip R.; Brown, Allan F.; Yousef, Gad G.; Ibrahem, Ragy; Anderson, Candice
Abstract: Tomato mosaic virus (ToMV) is an important Tobamovirus that causes significant crop losses. Resistance to the ToMV is conferred by the genes Tm1, Tm2 and Tm2 a . Among these three genes, Tm2 a confers resistance to most strains of the ToMV. Screening of genetic lines under field conditions based on phenotype is time‐consuming and challenging due to concerns associated with stability of the virus and its potential transmission to other plants. Tightly linked molecular markers associated with resistance genes can improve selection efficiency and avoid these problems. This study developed a PCR‐based marker based on restriction site differences from Tm2 a locus‐specific sequences, which was found to be useful in identifying the resistant and susceptible genotypes and was consistent with phenotypic data. The marker is a codominant cleaved amplified polymorphic sequence (CAPS) marker producing 270‐ and 600‐bp DNA fragments from resistant genotypes and an 870‐bp fragment from susceptible genotypes when digested with Hae III restriction enzyme. This novel marker can be useful for tomato breeders to screen progeny from segregating populations for ToMV resistance.